EI24 Inhibits Cell Proliferation and Drug Resistance of Esophageal Squamous Cell Carcinoma - Duan, Lili; Ma, Jiaojiao; Yang, Wanli; Cao, Lu; Wang, Xiaoqian; Niu, Liaoran; Li, Yiding; Zhou, Wei; Zhang, Yujie; Liu, Jinqiang; Zhang, Hongwei; Zhao, Qingchuan; et al. (Frontiers in Oncology, 2020)
Drug resistance, whether intrinsic or acquired, often leads to treatment failure in esophageal squamous cell carcinoma (ESCC). Clarifying the mechanism of drug resistance in ESCC has great significance for reversing drug resistance and improving the prognosis of patients. Previously, we demonstrated that etoposide induced 2.4 kb transcript (EI24) is the target of miR-483-3p which promoted the proliferation, migration and drug resistance of ESCC, which suggests that EI24 probably participate in tumorigenesis and progression of ESCC. Here we observed that EI24 was significantly decreased in ESCC tissues and its expression was positively correlated with the prognosis of patients. We then confirmed that the forced overexpression of EI24 inhibited cell proliferation and sensitized ESCC cells to chemotherapeutic agents, whereas EI24 silencing had the opposite effect. Furthermore, gene microarray and Ingenuity Pathway Analysis (IPA) analysis were performed to identify potential mechanisms and indicated that EI24 exerts tumor suppressive role via suppressing the acute phase response signaling pathway or IL-1 signaling pathway in ESCC. Taken together, our data suggest that EI24 overexpression attenuates malignant phenotypes of ESCC and could be used as a novel potential target for the treatment of ESCC.